Short-interval postconditioning protects the bowel against ischaemia–reperfusion injury in rats. (June 2017) - Ozkisacik, Sezen; Erdem, Ali Onur; Etensel, Barlas; Tataroglu, Canten; Serter, Mukadder; Yazici, Mesut
Objective: Acute mesenteric ischaemia leads to intestinal damage. Restoration of blood flow results in further damage to tissue, which is called reperfusion injury. This study aimed to investigate the protective effects of short-interval postconditioning and to determine the optimal interval for reperfusion in an experimental rat model of intestinal ischaemia. Methods: Forty adult male Wistar rats were grouped as follows: sham (Sh), ischaemia + reperfusion (IR), ischaemia + postconditioning for 5 seconds (PC5), ischaemia + postconditioning for 10 seconds (PC10), and ischaemia + postconditioning for 20 seconds (PC20). For postconditioning, 10 cycles of reperfusion (5, 10, or 20 seconds) interspersed by 10 cycles of 10 seconds of ischaemia were performed. Blood glutathione reductase (GR) and glutathione peroxidase (GPx) levels were measured. Intestinal tissue damage was assessed histopathologically. Results: GR levels were significantly higher in the PC5 group than in the IR group (37.7 ± 9.0 vs. 18.5 ± 2.0 min/g Hb). GPx levels were significantly higher in the PC10 group than in the IR group (43.2 ± 9.2 vs. 15.9 ± 4.6 U/g Hb). The histopathological score was significantly lower in the PC5 group (1.1 ± 0.1) than in the IR group (2.1 ± 0.2). Conclusion: Short-interval postconditioning reduces reperfusion injury in the ischaemic bowel and the optimal interval for reperfusion is 5 seconds. The long-term effects of short-interval postconditioning and the optimal reperfusion interval in intestinal ischaemia–reperfusion in rats need to be investigated.